Elaboración del manual de uso y mantenimiento de los equipos del laboratorio de interpretación turística para la carrera de ingeniería en ecoturismo de la ua-caren de la Universidad Técnica de Cotopaxi - Caza Caizaluisa, Cristina Elizabeth (2014)
This research was carried out in order to develop a manual. It allows a right use and preservation of different lab’s materials and equipment of tourist interpretation of the UA – CAREN. The big problem faced by IES is the absence of laboratories to improve of teaching-learning process. This problem is solved with a proposal based on 3 fundamental axes. It is given to know the methodology used in the present investigation. The first phase is a descriptive bibliographic research. The technique applied is an interview and an observation, which allows collecting essential information from manuals from different universities of Ecuador. The second phase includes Inductive and deductive method. Also, there was a fusion of manuals’ designs from different universities investigated taking into account the standards set for the responsible management of laboratory equipment. In the last phase, we use the deductive method and the technique of observation with the purpose to design a manual according….